2021
DOI: 10.1016/j.cegh.2021.100918
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of musculoskeletal disorders (MSDs) among weavers of Varanasi, India: A cross-sectional study

Abstract: Background: Work-related musculoskeletal disorders are widespread among workers in the weaving industry. The most affected body regions are the neck, shoulders, back, and wrist. The present study attempts to understand risk factors for MSDs in various body region among handloom and power loom weavers. Method: A cross-sectional household survey was conducted on a sample of 364 weavers during November 2019 to February 2020. The survey instrument for measuring musculoskeletal symptoms was adopted from a standardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
10
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 16 publications
7
10
4
Order By: Relevance
“…But in our study, LBP is 50%, and shoulder pain is 48%. In India, Siddiqui et al reported that 82% of handloom weavers have lower back pain (LBP), 48% have shoulder pain, and 60% have knee pain (Siddiqui et al, 2021). On the other hand, 84% of weavers have upper back pain (Siddiqui et al, 2021), whereas only 30% of weavers have upper back pain, according to our report.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…But in our study, LBP is 50%, and shoulder pain is 48%. In India, Siddiqui et al reported that 82% of handloom weavers have lower back pain (LBP), 48% have shoulder pain, and 60% have knee pain (Siddiqui et al, 2021). On the other hand, 84% of weavers have upper back pain (Siddiqui et al, 2021), whereas only 30% of weavers have upper back pain, according to our report.…”
Section: Resultssupporting
confidence: 64%
“…In India, Siddiqui et al reported that 82% of handloom weavers have lower back pain (LBP), 48% have shoulder pain, and 60% have knee pain (Siddiqui et al, 2021). On the other hand, 84% of weavers have upper back pain (Siddiqui et al, 2021), whereas only 30% of weavers have upper back pain, according to our report. Another research has been conducted by Neeraja et al They reported that 86% of handloom weavers suffer musculoskeletal pain (Neeraja et al, 2016).…”
Section: Resultssupporting
confidence: 64%
“…In this study, the overall annual prevalence of LBP among weavers was found to be 63.5% (95% CI = 58.8-68.5), which is lower than the annual prevalence of LBP among weavers in Arunachal Pradesh and Varanasi in India, Northern Thailand, and Belgium (i.e., 79.2, 82.91, 71, and 81%, respectively) (21,(47)(48)(49). The variation may be because the mean age of the participants in the current study was less than those of the participants in these four studies [38.79 (±12.844), 54.65 (±10.41), 57.21 (±3.15), and 39 (±9) years, respectively].…”
Section: Discussioncontrasting
confidence: 60%
“…In conclusion, preventive solutions should be implemented in the weaving sector to reduce the high prevalence of WRMSDs (Siddiqui et al 2021) and limit the occupational risk factors, especially because the resources to manage musculoskeletal conditions are limited in Africa (Ahenkorah et al 2019;KaborĂ©, Zanga & Schepens 2022). In addition, particular attention should be given to the informal sector, which is outside the systems that provide prevention, registration and compensation for occupational diseases (ILO 2013).…”
Section: Yarn Preparation By Walking (Kim-bm)mentioning
confidence: 99%